Biogas purification performance of new water scrubber packed with sponge carriers. (20th March 2019) - Noorain, Roslan; Kindaichi, Tomonori; Ozaki, Noriatsu; Aoi, Yoshiteru; Ohashi, Akiyoshi
Abstract: Water scrubbing technology is applied to biogas purification to obtain useful gas. However, it is difficult to produce highly purified gas of sufficient quality under typical operational conditions without imposing external pressure. Here, we propose a new water scrubber packed with sponge carriers instead of conventional packing materials, which has the advantage of increased hydraulic retention time for the scrubbing water. The results of biogas purification experiments indicate that the proposed scrubber can perform high purification even under atmospheric conditions. An artificial biogas of 60% methane is purified to more than 90% methane with no hydrogen sulfide detected; this quality level is acceptable for use as city gas. In addition, a mathematical model to simulate the purification phenomenon is constructed. Simulation experiments reveal that a high hydraulic retention time is very effective for good performance. We also found that the flow ratio of biogas to scrubbing water is the most crucial among the various operational parameters governing the purification performance. Graphical abstract: Highlights: A new water scrubber packed with sponge carriers is proposed. The technology proposed is feasible for biogas usage as city gas or vehicle fuel. Purification experiments using artificial biogas yield >90% CH4 concentration. Optimal operating conditions are determined based on experiment and simulation. High concentration of CO2 and H2 S eliminations from biogas.